In Vitro Efficacy of Domestic Techniques for Disinfection of Toothbrushes Contaminated With Enterococcus faecalis - Gina Alessandra Donayre-Salvatierra; Julissa Amparo Dulanto-Vargas; Raul M. Olaechea; Oscar Reátegui; Kilder Maynor Carranza-Samanez (Hindawi Limited, 2024)
Conclusions: Disinfection of TBs with CHX, WV, and MWs produces a significant effective reduction in the count of Ef.